2011
DOI: 10.1289/ehp.1002192
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Measurement of Brain GABA Concentrations by Magnetic Resonance Spectroscopy in Smelters Occupationally Exposed to Manganese

Abstract: BackgroundExposure to excessive levels of manganese (Mn) is known to induce psychiatric and motor disorders, including parkinsonian symptoms. Therefore, finding a reliable means for early detection of Mn neurotoxicity is desirable.ObjectivesOur goal was to determine whether in vivo brain levels of γ-aminobutyric acid (GABA), N-acetylaspartate (NAA), and other brain metabolites in male smelters were altered as a consequence of Mn exposure.MethodsWe used T1-weighted magnetic resonance imaging (MRI) to visualize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
120
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 139 publications
(135 citation statements)
references
References 45 publications
12
120
1
Order By: Relevance
“…Indeed, the dramatic increment of metal ranged between 16-68 folds in acute and 4-93 folds in chronic metal intoxication (Table 1). These observations mirror metal accumulation data in vivo in PD and Parkinsonism patients (Zecca et al 2005;Berg 2006;Dydak et al 2011) and poor clinical scores (Atasoy et al 2004). …”
Section: Discussionsupporting
confidence: 72%
“…Indeed, the dramatic increment of metal ranged between 16-68 folds in acute and 4-93 folds in chronic metal intoxication (Table 1). These observations mirror metal accumulation data in vivo in PD and Parkinsonism patients (Zecca et al 2005;Berg 2006;Dydak et al 2011) and poor clinical scores (Atasoy et al 2004). …”
Section: Discussionsupporting
confidence: 72%
“…In another study, reduced NAA : Cr was found only in the frontal cortex of Mn-exposed smelters, but not in the thalamus, putamen, or globus pallidus. 11 Additionally, a significant increase in GABA level, similar to the report of elevated GABA in globus pallidus tissue by Zwingmann et al, 84 was observed in a larger thalamus-centered volume of interest in the same study. 11 This finding of increased thalamic GABA has been reproduced in additional populations of smelters and welders in different countries and settings; 88-90 moreover, thalamic GABA levels were recently found to predict fine motor performance in Mn-exposed workers.…”
Section: Magnetic Resonance Spectroscopysupporting
confidence: 81%
“…11 Additionally, a significant increase in GABA level, similar to the report of elevated GABA in globus pallidus tissue by Zwingmann et al, 84 was observed in a larger thalamus-centered volume of interest in the same study. 11 This finding of increased thalamic GABA has been reproduced in additional populations of smelters and welders in different countries and settings; 88-90 moreover, thalamic GABA levels were recently found to predict fine motor performance in Mn-exposed workers. 89 Finally, Long et al also reported reduced Glu in the frontal cortex of Mn-exposed smelters and welders vs. matched controls, as well as reduced mI in the thalamus and posterior cingulate cortex.…”
Section: Magnetic Resonance Spectroscopysupporting
confidence: 81%
“…Prior to Fourier transformation of the MRS signal, 3 Hz exponential line broadening was applied. The difference-edited GABA signal at 3 ppm and the Cr peak from the unsuppressed MEGA-PRESS signal were fit with Gaussian and Lorentzian models, respectively (r > 0.95), and the area under these model fits was calculated to determine the GABA to total Cr ratio (GABA/Cr) (Edden and Barker 2007;Dydak et al 2011;Zhu et al 2011;Edden et al 2014).…”
Section: Neuroimaging Data Analysismentioning
confidence: 99%